2020
DOI: 10.1177/0143624420977749
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of free standing and building integrated grid connected photovoltaic system for southern part of India

Abstract: Photovoltaic (PV) system efficiency depends on the geographical location and the orientation of the building. Until installing the building structures, the integration of the PV module must be evaluated with ventilation and without ventilation effects. This work optimises the performance of the 250 kWp grid-connected photovoltaic (GPV) for community buildings in the southern part of India. This simulation is carried out to evaluate the system efficiency of the GPV system under various ventilation conditions, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Low cost, remarkably achievable analogically, and the ability of its easy integration with a DC/DC controller in various applications like the SPVWPS. FOCV method [16,17,19,21,[25][26][27], based on the use of reference voltage to adjust the duty ratio of the MPPT controller in a feedback control loop, supposes that irradiation and temperature variations on the array have not a significant impact on the MPP voltage value and that MPP voltage can be estimated with a predefined constant voltage V REF . Thus, the optimum voltage is always close to a proportion of the open circuit voltage V OC .…”
Section: 10mentioning
confidence: 99%
See 3 more Smart Citations
“…Low cost, remarkably achievable analogically, and the ability of its easy integration with a DC/DC controller in various applications like the SPVWPS. FOCV method [16,17,19,21,[25][26][27], based on the use of reference voltage to adjust the duty ratio of the MPPT controller in a feedback control loop, supposes that irradiation and temperature variations on the array have not a significant impact on the MPP voltage value and that MPP voltage can be estimated with a predefined constant voltage V REF . Thus, the optimum voltage is always close to a proportion of the open circuit voltage V OC .…”
Section: 10mentioning
confidence: 99%
“…Consequently, V REF can be calculated from the empirical relationship shown in Equation (31). It is found that the value of K varies between 72% and 78% [17,26].…”
Section: 10mentioning
confidence: 99%
See 2 more Smart Citations
“…PV technology is the appropriate technology to harness the solar energy. Integration of the solar photovoltaic technology into the building which converts the building from energy consumers into energy producer (Chandrika et al, 2020;Reddy et al, 2020). The 5-25% of incident solar radiation on the PV module converts the light energy into electrical energy and the remaining energy into heat.…”
mentioning
confidence: 99%